2016
DOI: 10.1002/cctc.201600858
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Nitroxide‐Catalyzed Oxidation of Amines: Preparation of Imines and Nitriles

Abstract: This Concept highlights the discovery and developments in the oxidations of amines catalyzed by TEMPO (2,2,6,6‐tetramethylpiperidinyl‐N‐oxyl) and related catalytic systems. The most important feature of these systems is that, with slight modifications in the reaction media, amines are selectively oxidized to either an imine or nitrile. Progress made toward the oxidation of various benzylic, allylic, and aliphatic amines, and possible reaction mechanism pathways are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…2,2,6,6-tetramethylpiperidine N-oxyl is widely known as an oxidation catalyst for alcohols, but it can also electrochemically oxidize amines [35]. However, the reaction is limited to organic solvents and basic aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2,2,6,6-tetramethylpiperidine N-oxyl is widely known as an oxidation catalyst for alcohols, but it can also electrochemically oxidize amines [35]. However, the reaction is limited to organic solvents and basic aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The nitroxyl radical moiety was oxidized at the electrode surface to an oxoammonium ion, which is the active form. The oxoammonium ion reportedly binds to a primary amine in aqueous solution resulting in the disappearance of catalytic activity [38][39][40] (Note: TEMPO oxidizes primary amines in acetonitrile [35]). Likewise, the oxoammonium ion of NNO bonds with ethylamine in aqueous solution causing the catalytic activity to disappear ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Stable nitroxyl radical TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) plays a salient role as catalyst in metal-, organo-or biocatalysed oxidation processes and signicant progress in terms of catalytic efficiency and substrate applicability has been achieved, 22 including oxidation of amines. 23 Concerning the bio-oxidation of amines, Contente et al reported an application of a ow-based biocatalysis in the oxidation of amines to aldehydes by an immobilized transaminase with sodium pyruvate as co-oxidant, 24 and Zheng et al reported the a-oxydation of cyclic amines to amides by whole-cell biotransformation. 25 Using metal-free oxidants, Gaspa et al reported a mild and solvent-free oxidation of primary amines to aldehydes, ketones, and nitriles by N-chlorosuccinimide under ballmilling conditions.…”
Section: Introductionmentioning
confidence: 99%